2010
DOI: 10.1510/icvts.2009.214437
|View full text |Cite
|
Sign up to set email alerts
|

Closed cardiopulmonary bypass circuits suppress thrombin generation during coronary artery bypass grafting☆

Abstract: Thrombin generation is considered unavoidable during cardiac surgery using cardiopulmonary bypass (CPB). We compared the effects of open and closed circuits on coagulation and fibrinolysis under identical conditions of priming volume, heparin-coating, and anticoagulation and transfusion protocols. Thirty coronary surgery patients were randomized to surgery using open circuits with open reservoirs and cardiotomy suction (open group, n=15) or closed circuits without either (closed group, n=15). In the closed gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Moreover, several studies have reported positive correlations between CPB duration and a negative influence on coagulation variables such as increased thrombin inhibition and fibrinolysis 18. Indeed, coagulopathy and increased bleeding are serious complications, particularly occurring after prolonged CPB,19,20 which is also associated with an increased risk of morbidity and mortality 21,22.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have reported positive correlations between CPB duration and a negative influence on coagulation variables such as increased thrombin inhibition and fibrinolysis 18. Indeed, coagulopathy and increased bleeding are serious complications, particularly occurring after prolonged CPB,19,20 which is also associated with an increased risk of morbidity and mortality 21,22.…”
Section: Discussionmentioning
confidence: 99%
“…58 Miniaturized circuits are associated with substantial reductions in neurologic injury, number of patients requiring transfusion of blood products, and peak cardiac troponin release.…”
Section: Extracorporeal Membrane Oxygenation (Ecmo)mentioning
confidence: 99%
“…D-dimer was used as a surrogate marker for fibrinolysis in this study [14]. As could be expected, according to the changes in serum levels of TAT, D-dimer levels developed in parallel.…”
Section: Commentmentioning
confidence: 57%
“…The TATas an indirect marker of thrombin generation, was chosen as a surrogate for coagulation activation in our setting [14]. Two hours after surgery, TAT was significantly higher in the Smart group as compared with the C.A.T.S.…”
Section: Commentmentioning
confidence: 99%